A new meroterpene lactone and a new alkyl amino alcohol from the Vietnamese marine sponge Hippospongia fistulosa Lendenfeld, 1889. Issue 4 (14th August 2021) - Hang, Dan Thi Thuy; Trang, Do Thi; Yen, Pham Hai; Cuc, Nguyen Thi; Dung, Duong Thi; Tai, Bui Huu; Nhiem, Nguyen Xuan; Van Kiem, Phan
Abstract: From the methanol extract of the marine sponge Hippospongia fistulosa Lendenfeld, 1889, a new meroterpene lactone named as hippolactone A (1 ), a new alkyl amino alcohol named as 2‐aminotetradec‐13‐ene‐3, 4, 5, 6, 7‐pentaol (2 ), and three known meroterpenes, polyfibrospongol A (3 ), polyfibrospongol B (4 ), and 19‐hydroxy‐polyfibrospongol B (5 ), were isolated. Their structures were elucidated by extensive spectroscopic analyses including IR, HR‐ESI‐MS, 1D and 2D NMR, and by comparison of the spectral data with those of previously reported data. Compounds 1 and 2 exhibited cytotoxic effects on Hep‐G2, MCF‐7, SK‐LU‐1, and SK‐Mel‐2 human cancer cells with percentages of dead cells in the range from 18.2±1.1 % to 43.4±1.6 %.